Numerical calculation of circulating current losses in stator transposition bar of large hydro‐generator. Issue 4 (1st July 2015) - Liang, Yanping; Bian, Xu; Yang, Lichao; Wu, Lei
Abstract : To reduce circulating current losses in stator strands of hydro‐generator, strand transposition is widely used in stator bars. At present, the traditional analytical method for calculating circulating current losses cannot accurately simulate the distribution of leakage magnetic field, which will bring a large deviation to the calculation result and not benefit the winding design. The numerical calculation method for circulating current losses in stator bar is presented in this study, by which the leakage magnetic field distribution of stator transposition bar can be described in detail through establishing three‐dimensional actual transposition model. The 0°/360°/0° transposition bar in a 180 MW hydro‐generator is taken as an example and the circulating current losses in stator bar strands are calculated. The causes of errors in traditional analytical method are discussed through the comparison of the leakage magnetic field distribution obtained by numerical calculation method and traditional analytical method.